Isolasi dan identifikasi bakteri patogen pada ikan nila (Oreochromis niloticus) yang dibudidayakan di Kecamatan Dimembe Kabupaten Minahasa Utara Tahun 2019 - Jr, Arfiandi; Tumbol, Reiny A. (Universitas Sam Ratulangi, 2020)
This study aimed to identify the type of pathogenic bacteria that attack tilapia (Oreochromis niloticus) cultivated in Dimembe District, North Minahasa Regency in 2019. The benefit of this research were to obtain information about the types of bacteria in tilapia (Oreochromis niloticus), so prevention efforts can be made or treatment of the disease. Tilapia as a research sample obtained from existing cultivation sites in the District of North Minahasa Dimembe, North Sulawesi Province. From each location 5-10 individuals were taken with a size of 5-12 cm. The samples were then taken to the laboratory for bacterial isolation. The media for growing bacteria was TSA (Tryptic Soya Agar). The results obtained were adjusted to the Bacterial Fish Pathogens identification book. The data obtained were analyzed descriptively through the presentation of tables and figures. Research results found the bacteria that infected tilapia in North Minahasa Regency including Aeromonas sp, Plesiomonas sp, Flavobacterium sp and Enterobacter sp. Regular and continuous monitoring of fish diseases is needed to monitor the spread of fish diseases, especially quarantine fish diseases in NorthÂ MinahasaÂ Regency.